When solving logarithmic/natural log equations, the strategy is to get ln (x) alone on one side, and all the stuff on the other side. Then exponentiate both sides to get to x.
2 ln (x + 3) = 0
ln (x + 3) = 0
At this point, we can't isolate anymore or use logarithm properties to separate this further. But we have ln (something), and we can exponentiate.
![e^(ln(x+3)) = e^(0)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/jwzj80wocrlad2s9ql7mxzuj6f17akeasx.png)
![e^(ln(x+3)) = 1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/9zj2376ynhagw3fmp9i7f4ly4449j3i5k5.png)
x+3 = 1 <--This come from the fact the ln (x) and
are inverse functions that undo each other. This is why exponentiating works.
x = -2
So x = -2 is our solution.